Wartość choroby w kontekście rodzinnym = The value of sickness in the context of family - Grondys, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author of the article The value of sickness in the context of family highlights that because of the sickness one has to reevaluate his or her goals in life. He also writes changes that happen within the family when a member - especially a child - is chronically sick. Backing his reflection with work of psychologists the author shows the differences on how the father and the mother get engaged in the life of a sick child. The author ponders upon families with disabled children pointing out various crises that are experienced both by parents and children in such situations. The author presents difficulties in functioning of such a family in larger society.
Keywords: zdrowie; choroba; niepełnosprawność; rodzina; relacje interpersonalne; health; illness; disability; family; interpersonal relations